Analysis of Noise and Vibration on Single Cylinder Four Stroke Engine with Green Diesel Fuel Based on Simulations - Beny Cahyono; Aguk Zuhdi M. Fathallah; Muhammad Hadrian Deswandi Jefrimananda; Semin Semin (Institut Teknologi Sepuluh Nopember, 2021)
One of the alternative and renewable energies is green diesel. Despite the fact that both use the same raw material, vegetable oil, the processes for producing green diesel and biodiesel are somewhat different. Green diesel is generated via the hydrotreating process, which involves injecting hydrogen gas into an oil to remove oxygen. The combustion process in the engine is influenced by the nature of the fuel. Green diesel fuel has a higher yield of material than biodiesel fuel. High pressure caused by combustion in the engine combustion chamber affects the vibrations and noises of diesel engines. By varying engine speed and load, this study compares noise and vibration produced by green diesel fuel to biodiesel B30 using a simulation process. The results showed that green diesel fuel produces more noise and vibration than biodiesel B30 fuel and that this is directly proportional to the pressure and power produced in the combustion chamber by the green diesel fuel combustion process. As the pressure in the combustion chamber rises, the explosion becomes more powerful, resulting in increased diesel engine noise and vibration.